Integrating Problem-Based Learning and Visual Media to Spark Science Curiosity in Fifth Graders - Pasaribu, Aweng Rovika; Siregar, Lis Yulianti Syafrida; Hasibuan, Nur Azizah Putri (Heca Sentra Analitika, 2024)
This research was motivated by students who observed low interest in science learning, negatively affecting their cognitive learning outcomes. The issue stems from the conventional, teacher-centered lecture method, resulting in one-way communication that causes students to become bored and disengaged. This study aims to enhance students' interest in learning by implementing the Problem-Based Learning (PBL) model supported by visual media for 5th-grade students at elementary school SD Negeri 100706 Padang Lancat in Padangsidimpuan City, North Sumatra, Indonesia. This research employs a collaborative Classroom Action Research approach with homeroom teachers. Data collection involved observation sheets and questionnaires. The findings indicate that the PBL model assisted by visual media significantly increased students' interest in learning science. Initial data revealed that only 26.67% of students were categorized as having a good interest in learning. In Cycle I, this percentage increased to 60%, and in Cycle II, it further rose to 87%, with students categorized as having good and very good interest in learning.